Ragam Cara Mengenalkan Ibadah Puasa Ramadhan bagi Anak Usia Dini - Rendy Setyowahyudi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
Fasting is a workshop which becomes a challenge for parents to introduce it to early childhood. The purpose of this study was to find out various ways of introducing Ramadan fasting to early childhood. This research is library research. The data was collected from library documents such as journal articles and the website that contain various ways of introducing Ramadan fasting to early childhood. The data analysis technique used content analysis by analyzing the content of a data message. The results of the study have found that there are four ways ways to introduce fasting to early children in fasting, using animated films and using storytelling methods